DIVERSITY OF CULTURABLE BACTERIAL COMMUNITY ASSOCIATED WITH THE CORAL Galaxea fascicularis FROM UJUNG KULON, INDONESIA - Agus Sabdono; Ocky Karna Radjasa; Rudiger Stöhr; Elena Zocchi (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Coral reefs are the most diverse marine ecosystems; however, little is known about their microbialdiversity in these ecosystems. The present study is aimed at investigating the general insights into thediversity of the bacterial community associated with the coral Galaxea fascicularis. A culture collectionof 45 bacteria associated with coral G. fascicularis from Ujung Kulon, Indonesia was established byplating on Zobell’s 2214E. Isolates were screened by means of RLFP and sequencing of representative16S rDNAs. Using the restriction enzyme HaeIII, isolates were classified into 8 pattern group. Thesequence results indicated that a high diversity of bacterial phylotypes was present within the coralGalaxea fascicularis. In general, there are three major groups of bacteria: (i) members of the division Firmicutes , (ii) Actinobacteria, and (iii) γ-proteobacteria. Phylogenetic data on microbial communitycomposition in coral G. fascicularis will help in the rational selection of culture conditions to improvethe diversity of bacteria and the knowledge on the physiological, biochemical, genetic, and molecularproperties of coral bacteria.